2017
DOI: 10.1021/acs.biomac.7b01115
|View full text |Cite
|
Sign up to set email alerts
|

Reproducible Dendronized PEG Hydrogels via SPAAC Cross-Linking

Abstract: A common issue with hydrogel formulations is batch-to-batch irreproducibility originating from poorly defined polymer precursors. Here, we report the use of dendritic polymer end-groups to address this issue and maintain reproducibility between batches of poly(ethylene glycol) (PEG) hydrogels. Specifically, we synthesized two end-functionalized PEG chains: one with azide-terminated first- and second-generation dendrons and the other with strained cyclooctynes. The two complementary azide and alkyne polymers re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…Whereas the rheological experiments were performed at 20 °C using NaH 2 PO 4 /Na 2 HPO 4 buffer (pH 8.0), additional experiments on the benchtop, in which separate polymer solutions in PBS at 37 °C were mixed into a rubber mold, demonstrated that the hydrogels also formed within seconds under physiological conditions. The gelation times are faster than those of previously reported dendrimer-based PEG[28], PEG/PAMAM[13] and PEG-polyglycerol[29] hydrogels where linear PEGs were employed as crosslinking agents. The rapid gelation of the 4-PEG-A/PAMAM and 8-PEG-A/PAMAM hydrogels is likely due to the high number of end groups on both PEG and PAMAM in combination with the efficient amidation reaction.…”
mentioning
confidence: 70%
“…Whereas the rheological experiments were performed at 20 °C using NaH 2 PO 4 /Na 2 HPO 4 buffer (pH 8.0), additional experiments on the benchtop, in which separate polymer solutions in PBS at 37 °C were mixed into a rubber mold, demonstrated that the hydrogels also formed within seconds under physiological conditions. The gelation times are faster than those of previously reported dendrimer-based PEG[28], PEG/PAMAM[13] and PEG-polyglycerol[29] hydrogels where linear PEGs were employed as crosslinking agents. The rapid gelation of the 4-PEG-A/PAMAM and 8-PEG-A/PAMAM hydrogels is likely due to the high number of end groups on both PEG and PAMAM in combination with the efficient amidation reaction.…”
mentioning
confidence: 70%
“…[46] Due to their minimally invasive nature, injectables and microneedle patches have lower complication rates than surgically implanted vehicles.T herefore, injectable hydrogels that crosslink through bioorthogonal reactions or physical transitions (e.g.,t emperature) are routinelyu sed as local delivery vehicles. [47,48] Biorthogonal crosslinking chemistries include aldehyde-hydrazide coupling, [49] Michael addition, [50] strain-promoted azide-alkynec ycloaddition (SPAAC), [51] inverse electron demandD iels-Alder (iEDDA) cycloaddition, [52] furan-maleimide Diels-Alder cycloaddition, [53] Schiff base formation, [54] thiolene/yne Michael addition, [55] or Staudinger ligation. [56] Physical crosslinking chemistries include guest-host interactions (e.g., adamantane with cyclodextrin, [57] methyl viologen and naphthoxy derivatives with cucurbiturils, [58] or by nucleoside base pairing [59] ), temperature-sensitive hydrophobic interactions, [48] peptides elf-assembly, [34] and ionic interactions.…”
Section: Implantation Methodsmentioning
confidence: 99%
“…Wichterle and Lim first described ethylene glycol monomethacrylate porous polymers with adjustable mechanical properties and water content in 1960, and they were successfully applied to contact lenses [ 43 ]. Then, studies on hydrogels shifted from a simple chemical single polymer network, such as poly(vinyl alcohol) (PVA), poly(ethylene glycol) (PEG), and poly(2-hydroxyethyl methacrylate) (pHEMA) [ 12 ], to the second generation hydrogels, stimulus-responsive hydrogels, as well as in situ hydrogel [ 44 ]. Nalbandian et al [ 45 ] prepared pluronic hydrogel which can be used as artificial skin for the treatment of full thickness thermal burns and control the release of antimicrobial silver nitrate or silver lactate.…”
Section: Design Of Hydrogels For Bone Tissue Engineeringmentioning
confidence: 99%